2006
DOI: 10.1623/hysj.51.5.864
|View full text |Cite
|
Sign up to set email alerts
|

Hydrometeorological reconstruction of the 1824 flood event in the Neckar River basin (southwest Germany)

Abstract: The integration of extreme historical floods in contemporary flood protection contributes towards improved risk management and safer handling of floods in the future. As a case study within the "Xfloods" project at the University of Freiburg (Germany), the discharges of the extreme flood in 1824 in the Neckar River basin (Baden-Württemberg/southwest Germany) were reconstructed using historical data. Quantitative and qualitative historical sources were applied to model the regional atmospheric circulation patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 18 publications
(18 reference statements)
1
50
0
1
Order By: Relevance
“…Several studies (e.g. Bürger et al, 2006;Haag et al, 2005;Ott and Uhlenbrook, 2004;Bronstert et al, 2003) have shown that on large scales land use influences on discharge values during advective hydrometeorological extreme events are relatively small. Therefore, the historical land use from 1882 was not considered for the LARSIM simulation.…”
Section: Run-off Simulation With Larsim and Meteorological Input Paramentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies (e.g. Bürger et al, 2006;Haag et al, 2005;Ott and Uhlenbrook, 2004;Bronstert et al, 2003) have shown that on large scales land use influences on discharge values during advective hydrometeorological extreme events are relatively small. Therefore, the historical land use from 1882 was not considered for the LARSIM simulation.…”
Section: Run-off Simulation With Larsim and Meteorological Input Paramentioning
confidence: 99%
“…The combination of rainfall and snow melt led to devastating floods, especially in tributaries of the Rhine River. In some parts of the Neckar catchment, the water levels were only exceeded by the extreme flood event in 1824 (Bürger et al, 2006).…”
Section: Reconstructed Atmospheric Circulation Pattern and Weather Comentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed overview of the collected and analysed data was given by Seidel et al (2009), Bürger et al (2006, Sudhaus et al (2008), Dostal et al (2007) and Straub (2007). The main difference between the datasets of 1824 and 1882 is the different quantity and quality of the meteorological measurements.…”
Section: Information From Regional Historical Meteorological Datamentioning
confidence: 99%
“…Schübler has published the daily precipitation amounts from five meteorological stations for the extreme flood event at the end of October and the beginning of November 1824 (Schübler, 1825). These data are still only fractional or unpublished and were firstly used by Bürger et al (2006). The location of the sites with meteorological measurements in 1824 is depicted in Figure 2 .…”
Section: Information From Regional Historical Meteorological Datamentioning
confidence: 99%